JARINGAN SOSIAL FORUM KOMUNIKASI USAHA MIKRO DALAM PEMASARAN DI KELURAHAN KOTA KULON KECAMATAN SUMEDANG SELATAN KABUPATEN SUMEDANG - Diana, Diana (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2024)
This study explores social network of the Micro Business Communication Forum in marketing for micro-enterprises in Kota Kulon Village, South Sumedang, Sumedang Regency. Using a qualitative approach with descriptive methods, this research highlights the forum's functions in information sharing, coordination, and access within the micro-enterprise community. Findings indicate that the forum effectively disseminates information related to business opportunities and aids coordination among members for training and promotions. It also provides access to resources like equipment and capital, fostering business growth. Despite its effectiveness, the forum faces challenges in expanding network access to meet the needs of all micro-businesses.